INTEGRATED LITERACY METHODS FOR THE DEVELOPMENT OF SOCIAL – EMOTIONAL SKILLS: PRE-SCHOOL GROUP CONTEXT - Tandzegolskienė-Bielaglovė, Ilona; Čiučiulkienė, Nijolė; Garbaravičienė, Jūratė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Preschool years are a significant period of a child's life, characterized by a unique social, artistic, cognitive, emotional expression of the child. In the preschool age, children go through a rather difficult period of development, which largely determines the success of their subsequent education at school. At this stage of development, children should feel the need to read and write and thus get to know the world (understand people's relationships, feelings, actions, intentions, etc.); should start reading and writing and feel the joy of reading and writing while successfully interacting with the surrounding world. Having mastered literacy skills, a child can express what he/she feels, hears, and sees. The received data were analyzed while using thematic content analysis. During the observation, it has cleared out that it is quite difficult for children to express their emotions. Practical tasks, such as acting situations, drawing emotions, activities with sand, discussions with parents and researchers when children try to express emotions, practically teach different ways to overcome everyday changes and difficulties and thus acquire social-emotional skills. An attractively equipped book reading area, interestingly used print encourages easier recognition of words and application of reading skills. The application of integrated literacy methods in the implementation of a preschool program is a suitable context for strengthening social emotional skills, which are crucial for recognizing and managing one's emotions, being empathetic, creating and maintaining positive relationships, setting and pursuing positive goals, and making responsible decisions. Literacy techniques such as printed environment, reading books, marking emotions, interactive writing and drawing, social stories, acting situations, and discussions are effective tools and ways to achieve these goals.